Experiences of Nurses during COVID-19 Pandemic: A Qualitative Study of Nepal - Panta, Ganga; Sharma, Sharada (Journal of Institute of Medicine Nepal, 2025)
Introduction Identification of the nurses’ experiences with regards to their personal, work and social situation, and timely addressed of their concern is crucial for the betterment of the health care. The objective of this study was to explore the experiences of nurses during the COVID-19 pandemic. Methods Qualitative design with a descriptive phenomenological approach was adopted for the study. Twenty nurses, who were working as front-liners during the COVID-19 pandemic in Tribhuvan University Teaching Hospital having at least six months experience in the COVID unit, were selected for an In-depth interview by adhering to interview guidelines. Colaizzi’s analysis method was used to analyze the data. Lincoln and Guba’s criteria were used for study rigor. Results The study identified the three main themes, which are chaotic environment, stigma and discrimination, and fear and anxiety. Nurses experienced a huge workload, terrible deaths due to the unavailability of oxygen, beds, ICU, and ventilators. They also experienced fear and anxiety of transmission of COVID-19 to their family members, including hesitation to disclose the working area and positive status as well as restrictions in gathering due to fear of discrimination. They realized that adequate support from their family and public appreciation helped them to gain self-esteem and recognition. Conclusion Nurses experienced a turmoil environment, a huge loss of life of people due to a lack of resources during the pandemic. Fear of transmission and social discrimination during the COVID-19 pandemic were other aspects affecting the nurses' daily lives. Thus, the adequate preparation of the health facilities to combat with such pandemic situations, including social awareness programs for the support of nurses, are crucial.